DETERMINANTS OF RURAL HOUSEHOLDS’ FOOD INSECURITY AND COPING MECHANISMS IN WESTERN AGRICULTURAL ZONE OF BAUCHI STATE, NIGERIA - Yusuf, F. A.; Abdullahi S.; Muhammed, R.; Garba M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
This study examined the determinants of rural households’ food insecurity and coping mechanisms in the Western Agricultural Zone of Bauchi State, Nigeria. A multi-stage and simple random sampling technique was used to select 212 rural households from two Local Government Areas Bauchi and Toro. Primary data collected through structured questionnaires were analyzed using descriptive statistics and linear regression. The results revealed that mean age of respondents was 36 years; majority were male (81.1%), married (75.9%), with a mean household size of 5 persons. Secondary education (32.5%) and crop farming (41.5%) were predominant among households. Linear regression showed that membership of cooperatives (P < 0.05) and frequency of extension contact (P < 0.05) were positive and significant in influencing food security among the respondents. Similarly, sex (P < 0.01) and access to extension (P < 0.05) were negative and significant in influencing food security. The most frequently cited constraints were lack of government support (57.1%), lack of awareness (46.7%), no assets to sell (20.3%), poor transportation (17.9%), and high cost of inputs (16.0%). It is concluded that food insecurity in the study area is significantly shaped by cooperative membership, extension contact frequency, and gender disparities. However, weak institutional support, poor awareness, and asset poverty severely limit households’ capacity to adopt effective coping strategies. Hence, it is recommended that respondents should strengthen and expand farmer cooperative societies with improved access to inputs, credit, and collective marketing, government should revitalize agricultural extension services through regular, gender-sensitive, and nutrition-focused training visits, establish targeted social safety nets (e.g., food assistance, subsidized inputs) for female-headed and asset-poor households.